A meta-analysis of the relationship between environmental tobacco smoke and lung cancer risk of nonsmoker in China. Issue 28 (July 2018) - Sheng, Lin; Tu, Jun-Wei; Tian, Jiang-Hua; Chen, Hui-Jun; Pan, Chu-Li; Zhou, Ren-Zhi
Abstract: Background: To investigate the association between exposure to environmental tobacco smoke (EVT) and the incidence of lung cancer (LC) in nonsmoking adults. Method: PubMed, Cochrane, Embase, Wanfang, CNKI, and VIP database were searched by the index words to identify the qualified case-control studies, and relevant literature sources were also searched. The latest research was done in June 2017. Odds radio (OR) along with 95% confidence interval (95% CI) were used to analyze the main outcomes. Result: Twenty RCTs were involved in the meta-analysis with 13, 004 adults in the case group and 11, 199 adults in the control group. The results indicated that compared with the nonexposure population, the risk of LC incidence was significantly higher in EVT exposure (OR: 1.64, 95% CI: 1.34–2.01), EVT male exposure (OR: 1.62, 95% CI: 1.16–2.28), EVT female exposure (OR: 1.57, 95% CI: 1.43–1.72), EVT exposure at workplace (OR: 1.78, 95% CI: 1.29–2.44), EVT exposure at home (OR: 1.53, 95% CI: 1.01–2.33), and EVT female exposure at home (OR: 1.55, 95% CI: 1.34–1.79). However, there is still no significant difference among the risk of LC incidence in EVT male exposure at workplace (OR: 1.51, 95% CI: 0.74–3.06), EVT female exposure at workplace (OR: 1.23, 95% CI: 0.99–1.53), and EVT male exposure at home (OR: 1.24, 95% CI: 0.68–2.26). Conclusion: EVT exposure is prospectively associated with a significantly increased risk of LC incidence. More high quality studies are required to address the association between EVT exposure and LC incidence.